2023
DOI: 10.1002/aic.18069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface roughness on methane hydrate formation and its implications in nucleation design

Abstract: As a new form of energy with substantial potential, natural gas hydrate will play a crucial strategic role in the future due to its vast reserves and broad industrial application prospects. To better comprehend the nucleation and growth mechanism of clathrate hydrate, an enhanced thermodynamic model was proposed based on the wall roughness model and nucleation theory. In general, we discovered that the nucleation of hydrate on a smooth wall surface conforms to the conclusion of classical nucleation theory. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…25 Li et al discovered that the impact of wall roughness on hydrate nucleation is extraordinarily complicated. 26 They reported that the hydrate nucleation was consistent with the classical nucleation theory on a smooth wall surface, while hydrophilicity promoted and hydrophobicity inhibited hydrate nucleation. Therefore, it is difficult to decouple the impact of solid walls from that of dilute electrolytes when they are present.…”
Section: ■ Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…25 Li et al discovered that the impact of wall roughness on hydrate nucleation is extraordinarily complicated. 26 They reported that the hydrate nucleation was consistent with the classical nucleation theory on a smooth wall surface, while hydrophilicity promoted and hydrophobicity inhibited hydrate nucleation. Therefore, it is difficult to decouple the impact of solid walls from that of dilute electrolytes when they are present.…”
Section: ■ Introductionmentioning
confidence: 58%
“…Bai et al carried out molecular dynamics simulations of CO 2 dissolved in water near silica surfaces and reported how the properties of solid surfaces impacted the local structures of the adjacent water molecules and the nucleation of gas hydrate . Li et al discovered that the impact of wall roughness on hydrate nucleation is extraordinarily complicated . They reported that the hydrate nucleation was consistent with the classical nucleation theory on a smooth wall surface, while hydrophilicity promoted and hydrophobicity inhibited hydrate nucleation.…”
Section: Introductionmentioning
confidence: 92%
“…37 (b) The near-perfect smooth surface of the fabricated microfluidic chip does not provide additional nucleation sites for MH heterogeneous nucleation. 38 Fig. 4c-h show the images acquired at location 1 (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the derived model is limited to capillary bundle model, which does not consider the surface roughness of HBCSS. In general, pore surfaces of HBCSS are not smooth and exhibit random roughness [87,88]. Secondly, although the derived model accounts for WC hydrates, PF hydrates, and the combination of these two hydrates, it ignores other hydrate patterns such as grain coating, lenses, and veins in HBCSS.…”
Section: Model Advantages and Limitationsmentioning
confidence: 99%